Labour migrant in Southeast Asia as non-traditional threat and efforts taken by ASEAN: an analysis / Nik Syamim Aisyah Nik Hashim - Nik Hashim, Nik Syamim Aisyah (2019)
Labour migration in Southeast Asia since the 1970s and 1980s must be understood as an integral part of the post-colonial new geographies of migration. The scope and scale of transnational movements have grown rapidly and major states like Malaysia and Thailand between them currently host about 70 percent migrant workers in the region. The phenomena characterize these labour movements legal and illegally within Southeast Asia countries. Like labour-importing Western democracies, the major Southeast Asian labour-importing countries rely on migrants to solve their labour shortage problems that locals refuse to fill. Hence, managing migration is a major problem facing these countries as the unemployment rate increase and it became a national threat for the countries. ASEAN strategies are very crucial to deal with this issue in minimizing the presence of migrants whether legal or illegal migrants. Therefore, this paper examines factors that contribute to labour migration in Southeast Asia and efforts taken by ASEAN to solve this problem.